Sex-specific positive and negative consequences of avoidance training during childhood on adult active avoidance learning in mice - Spröwitz, Almuth; Bock, Jörg; Braun, Katharina (Frontiers in Behavioral Neuroscience, 2013)
In humans and animals cognitive training during childhood plays an important role in shaping neural circuits and thereby determines learning capacity later in life. Using a negative feedback learning paradigm, the two-way active avoidance (TWA) learning, we aimed to investigate in mice (i) the age-dependency of TWA learning, (ii) the consequences of pretraining in childhood on adult learning capacity and (iii) the impact of sex on the learning paradigm in mice. Taken together, we show here for the first time that the beneficial or detrimental outcome of pretraining in childhood depends on the age during which TWA training is encountered, indicating that different, age-dependent long-term “memory traces” might be formed, which are recruited during adult TWA training and thereby either facilitate or impair adult TWA learning. While pretraining during infancy results in learning impairment in adulthood, pretraining in late adolescence improved avoidance learning. The experiments revealed a clear sex difference in the group of late-adolescent mice: female mice showed better avoidance learning during late adolescence compared to males, and the beneficial impact of late-adolescent pretraining on adult learning was more pronounced in females compared to males.